Injectable hydrogels based on poly(amino urethane) conjugated bovine serum albumin - Kiattikhun Manokruang (2018)
Poly(amino urethane) (PAU) conjugated bovine serum albumin (BSA) hydrogels were prepared in a sequential step synthesis. The synthesis included preparation of PAUs, acrylation of the synthesized PAUs and conjugation of PAUs to BSA. The conjugation reaction was confirmed by Fourier transform infrared spectrometry (FT-IR) and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The conjugate exhibited pH and temperature induced sol-gel phase transitions, facilitating the DOX-loaded conjugate solution to form gels at the physiological conditions. The release of DOX from the conjugate hydrogel proceeded without the initial burst and persisted over 5 weeks. The cytotoxicity results showed that the conjugate was non-cytotoxic, allowing uses of this material in bioapplications. © 2014 Elsevier B.V.